Chicken soup for the soul Christmas treasury for kids : a story a day from December 1st through Christmas for kids and their families - Canfield, Jack, 1944- (Health Communications, 2002)
A collection of stories for each day in December through Christmas Day, to rekindle the excitement of the season and remind us what Christmas is really about. Christmas is a wonderful time for kids-the anticipation of gifts under the tree, the aroma of once-a-year treats in the oven, the excitement of decorating for holiday festivities, the joy of being with family and friends, all the things that create warm memories that linger throughout our lives. Even big kids, better known as adults, eagerly await that first cup of eggnog, savor the scent of a fresh-cut pine tree, and delight in the discovery of that perfect present for a hard-to-please relative. Christmas is a time of celebrating traditions-those that have been in the family for years, as well as those just recently embraced. Chicken Soup for the Soul Christmas Treasury for Kids will start a new holiday tradition for kids of all ages. With twenty-five true stories-one for each day in December through Christmas Day-this unique treasury will rekindle the Christmas spirit every December first and keep it burning in the hearts of readers throughout the holiday season. As kids and their loved ones read these stories together, they'll realize that the best traditions are those the whole family can share. Kids will read about the "angels among us" who give selflessly to those in need. They'll learn that sometimes the best gifts aren't bought at a store. They'll discover that giving to others can be more joyous than getting everything on their list. And both kids and adults will find these stories wonderful reminders of the true meaning of Christmas and make this book a cherished reading tradition for generations to come.